LncRNA KCNQ1OT1 Sponges miR-206 to Ameliorate Neural Injury Induced by Anesthesia via Up-Regulating BDNF - Yao Y; Wang X; Gao J (Drug Design, Development and Therapy, 2020)
Yao Yao,* Xuesong Wang,* Jin Gao Department of Anesthesiology, Xiangyang Central Hospital, Affiliated Hospital of Hubei College of Arts and Science, Xiangyang 441021, Hubei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jin GaoDepartment of Anesthesiology, Xiangyang Central Hospital, Affiliated Hospital of Hubei College of Arts and Science, Jingzhou Street No. 39, Xiangcheng District, Xiangyang 441021, Hubei, People’s Republic of ChinaTel +86 15897965817Email ji84174603@163.comObjective: Widely used in anesthesia, ketamine is reported to induce neurotoxicity in patients. This study aimed to investigate the molecular regulatory mechanism of long non-coding RNA (lncRNA) KCNQ1 opposite strand/antisense transcript 1 (KCNQ1OT1) in ameliorating ketamine-induced neural injury.Materials and Methods: Sprague–Dawley rats were intraperitoneally injected with ketamine to induce neuronal injury. PC-12 cells treated with ketamine were used as the cell model. Ketamine-induced aberrant expression of KCNQ1OT1, miR-206 and brain-derived neurotrophic factor (BDNF) were examined by quantitative real-time polymerase chain reaction (qRT-PCR). The effects of KCNQ1OT1 and miR-206 on ketamine-induced neural injury in PC-12 cells were then examined by MTT and LDH assay. The regulatory relationships between KCNQ1OT1 and miR-206, and miR-206 and BDNF were detected by dual-luciferase reporter assay.Results: Ketamine induced the apoptosis of neurons of the hippocampus in rats, and the apoptosis of PC-12 cells, accompanied by down-regulation of KCNQ1OT1 and BDNF expressions, and up-regulation of miR-206 expression. Overexpression of KCNQ1OT1 enhanced the resistance to apoptosis of PC-12 cells and significantly ameliorated ketamine-induced nerve injury, while transfection of miR-206 had opposite effects. Mechanistically, KCNQ1OT1 could target miR-206 and reduce its expression level, in turn indirectly increase the expression level of BDNF, and play a protective role in neural injury.Conclusion: KCNQ1OT1/miR-206/BDNF axis is demonstrated to be an important regulatory mechanism in regulating ketamine-induced neural injury. Our study helps to clarify the mechanism by which ketamine exerts its toxicological effects and provides clues for the neuroprotection during anesthesia.Keywords: ketamine, neural injury, lncRNA KCNQ1OT1, miR-206, BDNF